Weltanschauung Religius-Nasionalis Kiai Tarekat dalam Tinjauan Teori Kritis - Iwan Kuswandi; Achmad As'ad Abd Aziz; Mudiuddin Mudiuddin (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2022)
This study examines the role of Kiai Djauhari as a practitioner of the Tijaniyah Order in the fight against colonialism, using a critical theory perspective. This research uses a qualitative historical approach. Data obtained from primary and secondary sources, then the researchers analyzed interpretively and comparatively. Conclusion, Kiai Jauhari is the pioneer of the nation's independence struggle and Kiai Djauhari is trying to build a community construction that has a spirit of nationalism. Kiai Djauhari's strategy in building public awareness to fight colonialism, namely with a religious approach, education to social organization. Mainly he did through the organization of the Tijaniyah Order.